The early derivative water mites (Acari: Hydrachnidia, superfamilies Eylaoidea, Hydrachnoidea and Hydryphantoidea) of Madagascar - Gerecke, Reinhard (Zootaxa, 2020)
A general introduction to the water mites of Madagascar is given, together with a survey of the diversity of the early derivative superfamilies Eylaoidea, Hydrachnoidea, and Hydryphantoidea. The family Teratothyadidae (genera Teratothyas and Teratothyasides) and the hydryphantid subfamilies Euthyadinae (genera Javathyas and Trichothyas) and Wandesiinae (genus Wandesia) are recorded for the first time from Madagascar, the latter being new for the Ethiopian bioregion. One subgenus in the family Teratothyadidae, Ascoteratothyas subgen. nov. (genus Teratothyas) and eighteen species are described as new to science: Hydrodroma amoenoderma, H. lasioderma, H. megalonyx, H. mesembrina, H. poseidon, Javathyas nasipalpis, Wandesia pelipoda, W. anjozorobensis, Teratothyas (s. str.) digitata, T. (s. str.) aucta, T. (s. str.) proceripapillata, T. (s. str.) planipapillata, T. (Ascoteratothyas) levigata, T. (A.) porrigens, T. (A.) reducta, Teratothyasides heptaplax, T. ravenala and T. vanilla. Previous Madagascan records of Hydrodroma despiciens (Müller, 1776) and H. capensis (K. Viets, 1914) are attributed to H. poseidon. The subgenus Pseudowandesia is synonymized with the nominate subgenus. New locality records for other species include the first recording on the island of Hydrodroma perreptans (K. Viets, 1913) and H. zhokhovi Tuzovskij, 2014. Limnochares connexa Tuzovskij & Gerecke 2009 is redescribed. A dichotomous key leads to species level for the groups treated here, to family level for representatives of the remaining four superfamilies present on Madagascar.